DNA marker techniques in study and selection of plant - Thanh, Nguyen Duc (Academia Journal of Biology, 2015)
Since the 1980s, DNA marker techniques have been invented and developed quickly to become the most significant development in the field of molecular biology. The DNA markers have been widely used in study and selection of plants. The DNA techniques have been developed for DNA markers used in studies of genetic diversity, phylogeny, classification, gene tagging and identification; in germplasm and marker-assisted selection. The presence of various types of DNA markers, and differences in their principles, methodologies, and applications require careful consideration in choosing one or more of such methods. No DNA markers are available that fulfill all requirements needed by researchers. Depending on the nature of each study, one can choose among the variety of DNA marker techniques, each of which combines at least some desirable properties. In Vietnam, the use of DNA marker techniques began at the end of 1990s. However, the application was limited with only few techniques such as random amplified DNA polymorphism, microsatellites or simple sequence repeats and amplified fragment length polymorphism. Those techniques were used in the studies of plant genetic diversity, molecular mapping and marker-assisted selection. This review provides an overview on most of the available DNA marker techniques and their utilities in the study and selection of plants with the aim to provide researchers and breeders necessary information for choosing appropriate DNA marker techniques.